1986
DOI: 10.1159/000281186
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hemorrhagic Cystitis Caused by Adenovirus Type 11 after Renal Transplantation

Abstract: A case of acute hemorrhagic cystitis caused by adenovirus type 11 which occurred in an allograft recipient 6 months after a living-related renal transplantation, is described. The patient lacked a neutralizing antibody to adenovirus type 11 before transplantation. Adenovirus type 11 was isolated from his urine and he developed a neutralizing and complement-fixing antibody to this virus. Although adenovirus type 11 isolates had been obtained from 2 of 18 renal allograft recipients, only 1 patient suffered acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Adll has been reported to be associated with upper or lower respiratory illness [10,[17][18][19], hemorrhagic cystitis in chil dren and young adults, especially in renal transplant recipients [7,8,[20][21][22][23][24], and ep idemic hemorrhagic conjunctivitis [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Adll has been reported to be associated with upper or lower respiratory illness [10,[17][18][19], hemorrhagic cystitis in chil dren and young adults, especially in renal transplant recipients [7,8,[20][21][22][23][24], and ep idemic hemorrhagic conjunctivitis [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, if the recipient had no antibody to the infecting virus but the donor did, the serologic data suggest that the virus was latent in the donor organ and proceeded to set up a new infection in the recipient. In LT (67,122) and RT (39,46,64,76,87,91,107,113) recipients, this has been the case more often than infection from reactivated endogenous virus.…”
Section: Adenoviruses In Primary Immunodeficienciesmentioning
confidence: 99%
“…Ad11, belonging to the species B adenoviruses, was originally isolated from the urinary tract and causes hemorrhagic cystitis in children (Numazaki et al, 1968;Shindo et al, 1986). We have previously shown that species B adenoviruses use two different receptors (Mei et al, 1998;Segerman et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%